Transformasi Motif Batik Bilik Garut dalam Pengembangan Tenun Tradisional - Marlianti, Mira; Arafah, Naufal; Zakiyah, Zumrotu; Asyifa, Naila Ummu (ATRAT: Jurnal Seni Rupa, 2024)
This study aims to analyze the transformation of the Bilik Garut batik motif in the context of traditional weaving development. Bilik Garut batik is known as one of the distinctive motifs from the Garut region, carrying significant historical and cultural value. Using a descriptive qualitative approach, this research explores the process of adapting and innovating the motif into traditional weaving products. Data were obtained through field observations, interviews with artisans, and literature reviews related to batik and traditional weaving. The findings show that the transformation of the Bilik Garut batik motif into weaving introduces a new aesthetic dimension that not only preserves local identity but also enhances the economic value of weaving products. This motif adaptation also plays an important role in preserving regional cultural heritage while creating more innovative products that appeal to both local and international markets. The study suggests the need for collaboration between designers, artisans, and local governments in promoting culturally-based products, while also strengthening the creative economy rooted in traditional heritage.